Combination of Epigallocatechin Gallate and Sulforaphane Counteracts In Vitro Oxidative Stress and Delays Stemness Loss of Amniotic Fluid Stem Cells. (17th December 2018) - Marrazzo, Pasquale; Angeloni, Cristina; Freschi, Michela; Lorenzini, Antonello; Prata, Cecilia; Maraldi, Tullia; Hrelia, Silvana
Abstract : Amniotic fluid stem cells (AFSCs) are characterized in vivo by a unique niche guarantying their homeostatic role in the body. Maintaining the functionality of stem cells ex vivo for clinical applications requires a continuous improvement of cell culture conditions. Cellular redox status plays an important role in stem cell biology as long as reactive oxygen species (ROS) concentration is finely regulated and their adverse effects are excluded. The aim of this study was to investigate the protective effect of two antioxidants, sulforaphane (SF) and epigallocatechin gallate (EGCG), against in vitro oxidative stress due to hyperoxia and freeze-thawing cycles in AFSCs. Human AFSCs were isolated and characterized from healthy subjects. Assays of metabolic function and antioxidant activity were performed to investigate the effect of SF and EGCG cotreatment on AFSCs. Real-time PCR was used to investigate the effect of the cotreatment on pluripotency, senescence, osteogenic and adipogenic markers, and antioxidant enzymes. Alkaline phosphatase assays and Alizarin Red staining were used to confirm osteogenic differentiation. The cotreatment with SF and EGCG was effective in reducing ROS production, increasing GSH levels, and enhancing the endogenous antioxidant defences through the upregulation of glutathione reductase, NAD(P)H:quinone oxidoreductase-1, and thioredoxin reductase. Intriguingly, the cotreatment sustained the stemness state by upregulating pluripotency markers such as OCT4 and NANOG. Moreover, the cotreatment influenced senescence-associated gene markers in respect to untreated cells. The cotreatment upregulated osteogenic gene markers and promoted osteogenic differentiation in vitro . SF and EGCG can be used in combination in AFSC culture as a strategy to preserve stem cell functionality.